(untitled) - Soderbaum, Fredrik (New York, 2003)
Theories of New Regionalismrepresents the first systematic attempt to bring together leading theories of new regionalism. Major theorists from around the world develop their own distinctive theoretical perspectives, spanning new regionalism and world order approaches along with regional governance, liberal institutionalism & neoclassical development regionalism, to regional security complex theory (RSCT) and the region-building approach.
Keywords: International economic relations,Regionalism,Globalization